Women in antiquity through the eyes of Plutarch - Antoniou, Zacharoula (Journal of Gender and Power, 2020)
This article deals with the writings of Plutarch and some of his radical views regarding women. Excerpts from Plutarch’s texts referring to female nature are studied and presented. The main issue that occupied Plutarch and many other authors of his era was the question of virtue, a purely philosophical concept deeply rooted in the ancient Greek culture. For this reason, some of Plutarch’s writings focus on the place of virtue in women’s society. Plutarch tries to prove that virtue exists equally in women, that women are dynamic, lawful wives who have the power to take matters into their own hands and who can perceive also the ultimate matter of friendship. This paper, therefore, seeks to show the other side of the coin regarding the position of women in antiquity, among Plutarch’s ethical essays, the Moralia.